2013
DOI: 10.1074/jbc.m113.449983
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 2 Ligands Regulate Monocyte Fcγ Receptor Expression and Function

Abstract: Background: Toll-like receptors recognize bacterial components, leading to immune activation. Results: TLR2 ligands alter monocyte/macrophage Fc␥R and phosphatase expression to improve function both in vitro and in vivo. Conclusion: TLR2 ligands enhance monocyte/macrophage function. Significance: Fc␥R function is critical for antibody therapy. Deciphering the effect of TLR2 ligands provides a potential means to enhance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
(33 reference statements)
2
21
0
Order By: Relevance
“…1A) showed that agonists for TLR4 and TLR8 almost completely eliminated Fc␥RIIb, whereas agonists for TLR9 showed modest effects. TLR2 agonists led to variable results, occasionally leading to a slight decrease but, more often, to a modest increase in Fc␥RIIb, which is in agreement with our earlier findings (47). We repeated this and examined the transcript levels of Fc␥RIIb and found similar results (Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…1A) showed that agonists for TLR4 and TLR8 almost completely eliminated Fc␥RIIb, whereas agonists for TLR9 showed modest effects. TLR2 agonists led to variable results, occasionally leading to a slight decrease but, more often, to a modest increase in Fc␥RIIb, which is in agreement with our earlier findings (47). We repeated this and examined the transcript levels of Fc␥RIIb and found similar results (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Sequences for Fc␥RIIa, Fc␥RIIb, and GAPDH were as described previously (47). Primer sequences to detect MARCH transcripts were as follows: MARCH3 forward, GCGAGGACGATGGAAATCCT; MARCH3 reverse, CTTGCATGACATACTGCGGC; MARCH7 forward, CAAGCACACGTGTCCGATTTA; MARCH7 reverse, TGGTCTCCGTCTTCTTCGGA; MARCH9 forward, AGAA-GGTCCAGATTGCTGCC; and MARCH9 reverse, GATGA-GGCCTATGCAGACGA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally this result in the uptake of TLR2 bound molecules and cellular activation of APCs (3032). TLR2 recognizes lipoteichoic acid (3335), zymosan (36, 37), and bacterial lipoproteins (3840).…”
Section: Tlr2 and Lipopeptidesmentioning
confidence: 99%
“…Activation of Fc␥R also elicits cytokine production by monocytes, which serves to activate other immune effectors, such as natural killer (NK) cells (2)(3)(4)(5)(6)(7)(8). This involves the activation of Src kinases and Syk and then branches to other mediators (9).…”
mentioning
confidence: 99%